Prevalence and Associated Symptoms of Helicobacter pylori Infection among Schoolchildren in Kassala State, East of Sudan - Mohammed Abbas; Faiza A. Sharif; Shamselfalah M. Osman; Abdallah M. Osman; Sulieman M. El Sanousi; Mamoun Magzoub; Mutasim E. Ibrahim (Interdisciplinary Perspectives on Infectious Diseases)
This study aimed to determine the prevalence of H. pylori infections among schoolchildren and investigate the associations between H. pylori seropositivity and existence of gastrointestinal symptoms. Methods. A prospective cross-sectional study was conducted during a period from January to December 2012 at Kassala state, east of Sudan. Schoolchildren from different primary schools were enrolled in the study. Sociodemographic characteristics and gastrointestinal symptoms were recorded from each child. A rapid immunochromatographic test was performed for the detection of H. pylori IgG antibodies. Data on patient demographic characteristics, clinical diagnosis, and findings of H. pylori infection were analyzed by simple descriptive statistics. Results. Among 431 schoolchildren, H. pylori seropositivity was found to be 21.8%. The majority of children (79; 84%) had BMI below the normal range. The most frequent symptoms associated with H. pylori infections were nausea (25.5%), followed by gastric pain (24.5%) and heart pain (20.2%). There were statistically significant differences in H. pylori seropositivity between boys and girls (p=0.003). Conclusions. The prevalence of H. pylori infection among schoolchildren in Kassala city has been documented. Although the majority of the disease was associated with several gastrointestinal symptoms, the role of infection in the etiology of abdominal symptoms needs further investigations.